EFEKTIVITAS BIMBINGAN KELOMPOK DENGAN MENGGUNAKAN METODE DISKUSI UNTUK MENINGKATKAN KEPERCAYAAN DIRI - Gusnawati T. Oinan; Fitria Kasih; Rici Kardo (Jurnal Manajemen Pendidikan, 2026)
This research is motivated by the phenomenon of low student confidence which has an impact on learning engagement, courage to speak up, and the quality of interaction in the classroom. The purpose of this study is to describe the level of confidence of students before and after being given group guidance services with discussion methods and to test the effectiveness of these services in increasing confidence. The research uses a quantitative approach with an experimental method through a one group pretest and posttest design. The sampling technique uses saturated sampling so that all participants are made research subjects. The data collection instrument is in the form of a confidence questionnaire that has gone through validity and reliability tests. Data analysis was conducted using percentage intervals to describe the categories of confidence levels, while service effectiveness testing was conducted using the t-test. The results showed that before treatment, students' confidence was in the categories of quite high, low, and very low. After being provided with group guidance services with the discussion method, the level of confidence increased and was in the categories of quite high, high, and very high. There is a significant difference between the condition before and after treatment. Thus, group guidance services using the discussion method were declared effective in increasing students' confidence at school.